KOMPARASI PENJUALAN OBAT PREKURSOR SEBELUM DAN SESUDAH INSPEKSI BPOM DI APOTEK KIMIA FARMA 61 VETERAN BANJARMASIN TAHUN 2017 - Noor Aisyah; Desi Rahmida; Mochammad Maulidie Alfiannor Saputera; Shela Puzi Dina (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Submission of pharmaceutical drug precursors for hard drugs to patients must be prescribed by a doctor. The use of inappropriate precursors can be misused for the manufacture of illegal narcotics and psychotropics, including Pseudoephedrine. The purpose of this study was to determine the comparison of the sales of pseudoephedrine precursor drugs, hard drug groups that used prescriptions and did not use prescriptions before and after the inspection of the BPOM. This research was conducted at Kimia Farma Pharmacy No. 61 Veteran Banjarmasin with descriptive method. The population taken in the study was the sale of precursor drugs containing pseudoephedrine hard drug, three months before and three months after the BPOM inspection. The samples in this study were data on drug sales in the KIS system, the drugs were Aldisa sr sr, Lapifed, SR Rhinos, Rhinofed, Trifed and Tremenza. Data analysis was the Mann Whitney U-test. The results showed that there was no difference in sales of hard drug precursor of the pseudoephedrine type using prescription before and after BPOM inspection based on the Mann Whitney U-test with a significance value of0.579(p>0.05), and there were differences in the drug sales that did not use prescription with a significance value of0,000(p <0.05).